Heat increases MDMA-enhanced NAcc 5-HT and body temperature, but not MDMA self-administration - Feduccia, Allison A. (2010)
There is concern that hot environments enhance adverse effects of 3,4-methylenedioxymethamphetamine (MDMA or “Ecstasy”). In this study, long-term (4-wks) daily MDMA self-administration sessions and an MDMA challenge test were conducted with rats under normal and high thermal conditions (23° or 32° C). During MDMA self-administration sessions, activity and body temperature were increased by heat or MDMA experience, while MDMA self-administration rates increased with experience, but were comparable between thermal conditions. At the MDMA challenge test (3.0 mg/kg, i.v.), in vivo microdialysis showed nucleus accumbens serotonin (NAcc 5-HT) and dopamine (DA) responses were significantly increased in both thermal conditions. In the heated environment, MDMA-stimulated 5-HT responses and core temperature (but not DA) were significantly greater than at room temperature. Though the heated environment did not acutely boost MDMA intake, exaggerated NAcc 5-HT responses to MDMA may result in 5-HT depletion; a condition associated with Ecstasy use escalation and neural dysfunctions altering mood and cognition.